Predatory States: Operation Condor and Covert War in Latin America - McSherry, J. Patrice (Rowman & Littlefield Publishers, 2012)
This powerful study makes a compelling case about the key U.S. role in state terrorism in Latin America during the Cold War. Long hidden from public view, Operation Condor was a military network created in the 1970s to eliminate political opponents of Latin American regimes. Its key members were the anticommunist dictatorships of Chile, Argentina, Uruguay, Bolivia, Paraguay, and Brazil, later joined by Peru and Ecuador, with covert support from the U.S. government. Drawing on a wealth of testimonies, declassified files, and Latin American primary sources, J. Patrice McSherry examines Operation Condor from numerous vantage points: its secret structures, intelligence networks, covert operations against dissidents, political assassinations worldwide, commanders and operatives, links to the Pentagon and the CIA, and extension to Central America in the 1980s. The author convincingly shows how, using extralegal and terrorist methods, Operation Condor hunted down, seized, and executed political opponents across borders. McSherry argues that Condor functioned within, or parallel to, the structures of the larger inter-American military system led by the United States, and that declassified U.S. documents make clear that U.S. security officers saw Condor as a legitimate and useful 'counterterror' organization. Revealing new details of Condor operations and fresh evidence of links to the U.S. security establishment, this controversial work offers an original analysis of the use of secret, parallel armies in Western counterinsurgency strategies. It will be a clarion call to all readers to consider the long-term consequences of clandestine operations in the name of 'democracy.'